(untitled) (Medico Legal Update, 2021)
The purpose of this study is to investigate the association between knowledge and attitude on quality of life among diabetic patients type 2 in Palestine. Method: A cross-sectional quantitative descriptive study that contains a sample of 120 diabetic patients were selected from Nablus hospitals and outpatient clinics to assess the level of knowledge and attitudes toward self-care and health-related quality of life. Results: The mean score of Michigan Diabetic Knowledge Test was 8.04±2.48 and this consider a moderate level. Of 120 diabetic patients, 27.5% had poor knowledge; 65.5% had moderate knowledge, and only 6.6 % had good knowledge. The mean for attitude score of all respondents was 125.4±10.57 and this consider a positive attitude. There was a significant positive association between knowledge, attitude with HRQol (P=0.00). The mean for HRQoL score was 0.72 and it represented a moderate level of quality of life. Conclusion: Level of knowledge scores and HRQol were moderate and attitude toward the disease was positive in type 2 diabetic patients in Palestine, and there was a strong association between knowledge, attitude on HRQoL.